Problematika Psikologis Kuliah Daring - Mahdia Fadhila; Maulida, Rika (Jurnal Studia Insania, 2023)
This research aims to map the psychological problems of online lectures at UIN Antasari. Through the survey method, selecting respondents using incidental sampling techniques, data collection using Google forms. The research results show that the main problems with online lectures are internet network access and living environmental conditions. This problem had an impact on the psychological condition of respondents, namely, in the cognitive aspect, the dominant admitted to experiencing confusion (50%), lack of self-confidence (20.4%), and loneliness (11.3%). In the emotional aspect, most people expressed feelings of worry (37.3%), anxiety (33.8%), and 12% of respondents experienced other problems such as boredom, overthinking, laziness, stress, normal and relaxed. Meanwhile, as many as 32.4% of behavioral aspects admitted to being unproductive, delaying work (23.2%) and blaming circumstances (16.2%). The most frequent physical complaint felt by students while attending online lectures was experiencing sleep problems, namely 58 people or 40.8%, 23.2% did not experience any physical conditions, 19% experienced bodily responses such as dizziness, nausea and vomiting. Keyword: Islamic Psychology; psychological problems; online lectures;